Trajectory Planning For Autonomous Wheeled Mobile Robots With Trailer. Issue 2 (2020) - Essaidi, A. Bouzar; Lakhal, O.; Coelen, V.; Belarouci, A.; Haddad, M.; Merzouki, R.
Abstract: This paper presents a dynamic optimization scheme for generating trajectory planning for autonomous wheeled mobile robots with tractor designed to accomplish missions in indoor environments. Such an optimization criterion problem requires a method that can yield a fast execution time and minimum traveling distance that contains geometrics, kinematics, and physical/environment constraints. The main goal is to develop optimal trajectories planning approach of an autonomous wheeled mobile robots with trailer for the execution of predefined tasks in structures environment. The developed approach can be considered as an extension of the Random Profiles Approach used for wheeled mobile robots. The results also illustrate that thanks to its time optimal trajectories planning, our scheme is well adapted to complex tasks as it can get shorter execution time for the autonomous holonomic tractor with a nonholonomic trailer.